(3GdfaMI GdfSQjfjI hGddeMI GdeQjfjIs - (3GHf GdCMeQ , ESeGYjd Hf jhSa Hf eMeO Hf fUQ GdNRQLj GdfUQj, CHh GdhdjO,J (B807 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi aVd Cgd GdJGQjN HYedge CfHGA ef eVQi HGdbQGAI hGdYQV LYdJ JGQjNI ai GdOhdI GdeQjfjI PcQJ ef ajg ef Gdedhc HUaGJge hHYOO CjGege Edi Mjf haGJge s
(3BNQgG (B:s
(3jfJgi HJQLeI (B( (3CHh GdYHGS CMeO Hf CHj SGde Hf GdMSf Hf YKeGf Hf jYbhH Hf YHO GdMb hgh GdBf edc GdeZQH CjOg Gddg Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B329s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3MGdI GdfSNI SjFI s
Keywords: (3GdJGQjNs